Fracture Criteria Assessment in Adhesive Joint Modelling by XFEM - Guilherme J. C. Pinheiro; Raul D. S. G. Campilho (Current Approaches in Engineering Research and Technology Vol. 4, 2024)
Scarf adhesive joints find application in high-responsibility structures, including composite structures, due to their high efficiency. In this case, one of the most relevant geometric parameters is the scarf angle (\(α\)). The main objective of this work is to carry out a study to estimate the mechanical behavior of scarf adhesive joints as a function of \(α\) and the type of adhesive. Thus, an experimental and numerical study of scarf joints was carried out using the extended Finite Element Method (XFEM), in which different adhesives were applied. Aluminum (AW6082-T651) adherends were used in joints with different \(α\), being subjected to a tensile load. The values obtained experimentally and numerically were compared for each of the adhesives and \(α\) to validate the XFEM numerical method for determining the mechanical behavior of adhesive joints. The XFEM was validated for specific damage initiation and propagation criteria.